Effect of iron concentration on growth, protein content and total phenolic content of chlorella sp. cultured in basal medium - Dian Ariani,; Orasa Suriyaphan,; Nittaya Chaiyanate, (Universiti Kebangsaan Malaysia, 2011)
The aim of this study was to determine the effect of Fe3+ concentration (0.35, 4.89, 9.44 and 13.99 mg/L) on the growth, protein content and total phenolic content of Chlorella sp. The Chlorella sp. cells were grown at 51% relative humidity, 25°C ± 2 under continuous illumination at 36 W irradiance supplied by day-light fluorescent lamp, and agitated by bubbling at a flow rate 2.7 m/s2. Samples were collected every 2 days over 21 days of the cultivation period to estimate the growth of Chlorella sp. Protein and total phenolic content of samples were determined on phase 7th, 14th, and 21st day of cultivation. Statistical analysis showed that there were significant differences (p<0.05) on growth, protein content and total phenolic content of Chlorella sp. at different iron concentrations. These differences could be related to specific differences in the cell metabolism. Protein content (8.34 mg/g dry weight), total phenolic content (8.70 mgGAE/g dry weight), cell number (1.03 × 107 cell/mL) and the specific growth rate (μ) of Chlorella sp. (1.85/day) were highest at the lowest Fe3+ concentration (0.35 mg/L).